Inhibition of Tau Aggregation by Three Aspergillus nidulans Secondary Metabolites: 2,ω-Dihydroxyemodin, Asperthecin, and Asperbenzaldehyde - Paranjape, Smita R.; Chiang, Yi-Ming; Sanchez, James F.; Entwistle, Ruth; Wang, Clay C. C.; Oakley, Berl R.; Gamblin, T. Chris (Planta Medica, 2014)
The aggregation of the microtubule-associated protein tau is a significant event in many neurodegenerative diseases including Alzheimerʼs disease. The inhibition or reversal of tau aggregation is therefore a potential therapeutic strategy for these diseases. Fungal natural products have proven to be a rich source of useful compounds having wide varieties of biological activity. We have screened Aspergillus nidulans secondary metabolites containing aromatic ring structures for their ability to inhibit tau aggregation in vitro using an arachidonic acid polymerization protocol and the previously identified aggregation inhibitor emodin as a positive control. While several compounds showed some activity, 2,ω-dihydroxyemodin, asperthecin, and asperbenzaldehyde were potent aggregation inhibitors as determined by both a filter trap assay and electron microscopy. In this study, these three compounds were stronger inhibitors than emodin, which has been shown in a prior study to inhibit the heparin induction of tau aggregation with an IC50 of 1–5 µM. Additionally, 2,ω-dihydroxyemodin, asperthecin, and asperbenzaldehyde reduced, but did not block, tau stabilization of microtubules. 2,ω-Dihydroxyemodin and asperthecin have similar structures to previously identified tau aggregation inhibitors, while asperbenzaldehyde represents a new class of compounds with tau aggregation inhibitor activity. Asperbenzaldehyde can be readily modified into compounds with strong lipoxygenase inhibitor activity, suggesting that compounds derived from asperbenzaldehyde could have dual activity. Together, our data demonstrates the potential of 2,ω-dihydroxyemodin, asperthecin, and asperbenzaldehyde as lead compounds for further development as therapeutics to inhibit tau aggregation in Alzheimerʼs disease and neurodegenerative tauopathies.
Keywords: tau; microtubule-associated protein; Trichocomaceae; Aspergillus nidulans; Alzheimerʼs disease